CRITICAL STUDY ON THE INVESTIGATIONS REGARDING THE MORISCOS AND THEIR LEGACY: FROM THE FOUNDING SCHOOL TO THE NATIONALIST CURRENT - Zakaria, Marchoud (2020)
The present study deals with the Moriscos studies and their legacy in Spanish historiography. The objective aims to present in a chronological basis, the Spanish intellectual tendencies that marked the Moriscos studies and their criticism. The article deals with the founding school and the enormous role it played in the discovery and dissemination of the manuscript; as well as the nationalist era where the study of Moriscology reaches considerable intellectual maturity. Likewise, their successes and errors are pointed out through a firm terminological criticism. To do this, a systematically analytical method is applied. First of all, the main studies carried out in Spain about the Moriscos and their literary production are compiled, to proceed with their criticism. Thus, it is intended to demonstrate that, although the Spanish school contributed enormously to the development of Moriscology as a discipline, a crucial turn is needed in the study of the Moriscos to infuse more scientific rigor to this issue.